Production of kiwifruit is a profitable venture - Kumar, Ashok; Avasthe, R K; Borah, Tasvina R (Indian Horticulture, 2019)
The cultivation of kiwifruit in hilly tracts is not yet exploited up to its full potential. Studies on location-specific cultivation practices and development of processing industry in hilly areas are need of the hour. Research and extension activities related to kiwifruit should proceed concurrently for achieving fruitful outcome in the near future.